Synthesis, reactions and applications of naphthofurans: A review - Abdelwahab, Ashraf Hassan Fekry; Fekry, Salma Ashraf Hassan (European Journal of Chemistry, 2021)
Considering the highly important biological and medicinal properties of naphthofurans, the synthesis of these heterocycles has attracted the interest of medicinal and organic chemists. This review aims to describe the different strategies developed so far for the synthesis of naphthofurans and their applications and the literature reports for the period of 2000 to early 2020. After a brief introduction of the types of naphthofurans and their biological activities, the different synthetic approaches such as chemical and photochemical, methods are described and organized on the basis of the catalysts and the other reagents employed in the syntheses. Some of the reactions have been applied successfully to the synthesis of biologically important compounds.